2011
DOI: 10.1021/bi200936n
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of Function to Histidines 260 and 298 by Engineering the E1 Component of the Escherichia coli 2-Oxoglutarate Dehydrogenase Complex; Substitutions That Lead to Acceptance of Substrates Lacking the 5-Carboxyl Group

Abstract: The first component (E1o) of the Escherichia coli 2-oxoglutarate dehydrogenase complex (OGDHc) was engineered to accept substrates lacking the 5-carboxylate group by subjecting H260 and H298 to saturation mutagenesis. Apparently, H260 is required for substrate recognition, but H298 could be replaced by hydrophobic residues of similar molecular volume. To interrogate whether the second component would enable synthesis of acyl-coenzymeA derivatives, hybrid complexes consisting of recombinant components of OGDHc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 21 publications
(47 reference statements)
1
43
0
Order By: Relevance
“…7C). The spectra were reminiscent of analogous experiments with phosphonate analogs (10,24), and the positive CD band observed at 302 nm could be assigned to the 1Ј,4Ј-iminopyrimidine tautomer of the MSP-ThDP adduct. The titration data fit to Equation 2 revealed hyperbolic binding characteristics (n ϭ 1.0) with K d ϭ 575 Ϯ 38 M, similar to the K m 2KG of 570 Ϯ 80 M for 2-ketogutarate (Fig.…”
Section: Effect Of Allosteric Regulators On Accumulation Of Predecarbmentioning
confidence: 72%
See 1 more Smart Citation
“…7C). The spectra were reminiscent of analogous experiments with phosphonate analogs (10,24), and the positive CD band observed at 302 nm could be assigned to the 1Ј,4Ј-iminopyrimidine tautomer of the MSP-ThDP adduct. The titration data fit to Equation 2 revealed hyperbolic binding characteristics (n ϭ 1.0) with K d ϭ 575 Ϯ 38 M, similar to the K m 2KG of 570 Ϯ 80 M for 2-ketogutarate (Fig.…”
Section: Effect Of Allosteric Regulators On Accumulation Of Predecarbmentioning
confidence: 72%
“…Dithiothreitol (DTT) was from USB Corp. (Cleveland, OH), and isopropyl ␤-D-1-thiogalactopyranoside was from Denville Scientific (Metuchen, NJ). Methyl succinyl phosphonate (MSP) disodium salt was synthesized as reported (10). The synthesis of [C2,C6Ј- 13 C 2 ]ThDP has been reported (11).…”
Section: Methodsmentioning
confidence: 99%
“…16 Methyl acetylphosphonate (MAP) was synthesized using trimethylphosphite and acetylchloride as reagents according to Kluger et al 17 Purity and correct synthesis of all compounds were confirmed by NMR spectroscopy and mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, saturation mutagenesis experiments carried out at histidine-260 and histidine-298 [selected on the basis of the X-ray structure which suggested that these residues are near the -carboxylate binding site of 2-γ oxoglutarate (2-OG)] revealed that while H260 is important for catalysis, H298 could be substituted by a number of hydrophobic residues with little loss of activity. [8] We here report important extensions of the carboligation studies with E1o, where both the 2-oxoacid and the acceptor aldehyde could be varied over a wide range of reactivity, greatly adding to the versatility of E1o for carboligase reactions (Figure 1). The products and enantiomeric excess (ee) were confirmed by circular dichroism (CD), 1 H nuclear magnetic resonance (NMR), and chiral gas chromatography (GC).…”
Section: Introductionmentioning
confidence: 97%
“…Our synthetic program was initiated by making substitutions of the enzyme at the putative binding site of the γ-carboxyl group of the substrate so that the enzyme would accept substrate analogues lacking the charged γ-carboxyl group. [8] The Rutgers group has previously constructed several active site variants in yeast pyruvate decarboxylase (YPDC) from Saccharomyces cerevisiae and in the E1 component of the Escherichia coli pyruvate dehydrogenase complex (E1p) which were capable of catalyzing such reactions. [9] The E477Q YPDC variant was an effective acetoin synthase, while the D28A or D28N YPDC variants catalyze acetolactate formation.…”
Section: Introductionmentioning
confidence: 99%